Local Wisdom Values in Sayu Wiwit Folklore as The Revitalization of Behavioral Education - Fatimah, Firdauzia Nur; Sulistyo, Edy Tri; Saddhono, Kundharu (KARSA: Journal of Social and Islamic Culture, 2017)
This article attempts to describe the value of local wisdom found in Sayu Wiwit folklore as a means for revitalizing behavioral education. This study is conducted by using qualitative descriptive approach with the object of research is the value of local wisdom in Sayu Wiwit folklore. The researcher obtains the primary data through observation and direct communication with the respondents in the form of interviewing historians and experts in culture. Furthermore, the data of this study were analyzed by using flow analysis model, these are the following steps: (1) data collection, (2) data reduction, (3) data display, (4) conclusion drawing. The findings show, the values of local wisdom that can be taken from the folklore Sayu Wiwit are confidence, creativity, and behavior that suggested not giving up easily. The manifest of behavioral education can be seen through the values of local wisdom in Sayu Wiwit story, such as nationalism. The behavior and attitude of the main characters reflect the feeling of  and care about the country. Those attitudes is showed in the form of the confidence of the characters in Sayu Wiwit story that they do not give up and they tend to be creative when they try to defeat the invaders (Netherland) in Belambangan. The story of Sayu Wiwit  is considered as a historical story because it is told orally and this story can be verified with some historical evidences. Puputan Bayu Monument which is located Bayu Village, Songgon District and the name one of heroes who participated in that war is Mas Ayu Wiwit are the several historical evidences. Thus, the values of local wisdom from the folklore can be applied as a behavioral education to foster and develop the spirit of nationalism and patriotism in students.Copyright (c) 2017 by KARSA. All right reserved DOI: 10.19105/karsa.v25i1.1266